IMPRESI ORANG RIMBA: “MELANGUN” SEBUAH KOMPOSISI MUSIK DALAM INTERPRETASI PERJALANAN ORANG RIMBA - Hadaci Sidik (Puitika, 2016)
Orang Rimba is classical, one-part composition for orchestra, inspired by Orang Rimba’s tradition and characteristic style of life. Melangun is an obligation to move from one place to another in a case of serious threat or death one of the tribe members. Development of knowledge, technology and constantly growing human needs affect the Orang Rimba’s life cycle. Illegal logging, huntings, factory building, development of human settelemnents, palm and rubber plantations slowly destroy natural Kubu’s environment. Keywords: orang rimba, Melangun, komposisi musik